Combination Therapy of Oral Tofacitinib with Phototherapy in Severe Pediatric Atopic Dermatitis - Ananya Pramanik; Maitreyee Panda; Subhasree Madhual; C. V. V. Asritha (Wolters Kluwer Medknow Publications, 2024)
Atopic dermatitis (AD) is an itchy skin condition commonly seen in children. It is usually controlled with emollients and topical corticosteroids, but severe cases require systemic management. Tofacitinib is a promising molecule tried in various inflammatory dermatoses. It suppresses the expression of cytokines and improves the skin barrier function. Phototherapy is a second-line treatment modality in AD. Here, we describe a case report of a 6-year-old child of severe AD with predominantly lichenified lesions not responding to the conventional first-line therapeutics and cyclosporine. A combination therapy of tofacitinib with narrow-band ultraviolet B phototherapy (NB-UVB) was tried with impressive results in terms of symptomatic relief of pruritus and significant reduction in lichenification of the lesions.